Supporting of water reservoir restoration processes by selected type of biological beds - Agata Mazur; Krzysztof Chmielowski (Acta Scientiarum Polonorum. Formatio Circumiectus, 2021)
Aim of the study: The work aims to assess the possibility of the application of selected types of biological beds to support the revitalization processes of strongly degraded water reservoirs.